Magnetically Guided Capsule Endoscopy in Pediatric Patients with Abdominal Pain - Mingping Xie; Yuting Qian; Shidan Cheng; Lifu Wang; Ruizhe Shen (Gastroenterology Research and Practice)
Background and Aims. Magnetically guided capsule endoscopy (MGCE) offers a noninvasive method of evaluating both the gastric cavity and small intestine; however, few studies have evaluated MGCE in pediatric patients. We investigated the diagnostic efficacy of MGCE in pediatric patients with abdominal pain. Patients and Methods. We enrolled 48 patients with abdominal pain aged 6–18 years. All patients underwent MGCE to evaluate the gastric cavity and small intestine. Results. The cleanliness of the gastric cardia, fundus, body, angle, antrum, and pylorus was assessed satisfactorily in 100%, 85.4%, 89.6%, 100%, 97.9%, and 100% of patients, respectively. The subjective percentage visualization of the gastric cardia, fundus, body, angle, antrum, and pylorus was 84.8%, 83.8%, 88.5%, 87.7%, 95.2%, and 99.6%, respectively. Eighteen (37.5%) patients had 19 gastrointestinal tract lesions: one esophageal, three in the gastric cavity, and 15 in the small intestine. No adverse events occurred during follow-up. Conclusions. MGCE is safe, convenient, and tolerable for evaluating the gastric cavity and small intestine in pediatric patients. MGCE can effectively diagnose pediatric patients with abdominal pain.